(untitled) (Statistics, Optimization & Information Computing, 2023)
Extropy is a measure of the uncertainty of a random variable. Motivated with the wide applicability of quantile functions in modeling and analyzing statistical data, in this paper, we study quantile version of the extropy from residual lifetime variable, "residual quantile extropy" in short. Unlike the residual extropy function, the residual quantile extropy determines the quantile density function uniquely through a simple relationship. Aging classes, stochastic orders and characterization results are derived, using proposed quantile measure of uncertainty. We also suggest some applications related to (n i + 1)-out-of-n systems and distorted random variables. Finally, a nonparametric estimator for residual quantile extropy is provided. In order to evaluate of proposed estimator, we use a simulation study.